The Effectiveness of Group Reality Therapy on the Psychological Well-being of students - masoud fazlalipour; mohamad khalediyan; mehdi salehi (Journal of Social Behavior and Community Health)
Background: Reality therapy aims to foster responsibility-taking and help individuals establish a successful identity. This study investigates the effectiveness of group reality therapy on students' psychological well-being. Methods: The study population comprised all Payame Noor University students enrolled at Ghorveh branch during 2022. The research employed an experimental design with both experimental and control groups. A random sample of 30 students was selected, with 15 participants assigned to the experimental group, which received nine 90-minute sessions of group reality therapy. The remaining 15 students formed the control group. Data were collected using Carol Ryff's Psychological Well-Being Scale. Results: The findings showed descriptive information regarding psychological well-being in pretest and posttest for both control and experimental groups. Psychological well-being mean value of students in experimental group in pretest was 308.01 ± 9.38, while posttest mean value for the same group was 317.73 ± 8.99. In contrast, psychological well-being mean value of students in control group in pretest was 309.93 ± 8.84, with posttest mean value for this group being 310.46 ± 8.96. The findings revealed that group reality therapy significantly improved the students' psychological well-being (p < 0.05). Conclusion: Group reality therapy is an effective intervention for enhancing students' psychological well-being, Therefore, this method can be used to improve the psychological well-being of students.